EFEKTIVITAS LAYANAN PENGUASAAN KONTEN DALAM MENGATASI KESULITAN BELAJAR SISWA - Nurreza Saputri; Basri Basri; Teuku Fadhli (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
This research is motivated by the emergence of students who have learning difficulties, by showing behavioral symptoms when studying, for example students find it difficult to absorb lessons, do not concentrate when studying, go in and out when studying and so on. Problems with student learning difficulties at school require content mastery services that allow students to understand and develop good study attitudes and habits, learning skills and materials that match their learning speed and difficulty, as well as the demands of abilities that are useful in everyday life. The purpose of this study was to determine the implementation of content mastery services in overcoming the learning difficulties of class X students of SMA Negeri 1 Sakti. Research includes experimental research. The main subjects in this study were 60 people, namely 60 students of class X SMA Negeri 1 Sakti who participated in content mastery services in overcoming learning difficulties. The instrument used is a Likert scale model. Hypothesis testing using t-test. Based on the results of statistical analysis using the t-test, it can be seen that the value of tcount shows a significant difference (where tcount ttable) which is 2.01 1.67, so from the test criteria Ha is accepted, meaning that Content Mastery Services are effective in overcoming students' learning difficulties. class X SMA Negeri 1 Sakti.Keywords: Content Mastery Services, Learning Difficulties